(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Names have been used for centuries to communicate various messages to the world around. Among the Vatsonga, names have been considered critical badges that communicated the circumstances around a child’s birth, the behaviour or idiosyncratic tendencies of an individual, the descriptions of one’s physical stature, among other things. Naming in the real, concrete world, is an enormous, but critical undertaking that when done in a professional manner, speaks volumes in the provision of cultural and historic reservoirs. Naming in literature is equally relevant since it is the transfer of real world traditions into written forms, but still portraying the same values honoured and cherished by the people targeted for readership. This paper explores the significance of some of the names found in Mabuza’s drama text, Nyuku wa Mbyana. Purposive sampling has been used in the choice of names that the writer felt would better unravel the literary naming traits and patterns adopted by the author – in respect of Tsonga general-cum-literary naming traditions.